The Relationship of Blood Asprosin Levels and Biochemical Parameters in Pregnant Cows - Kılınç, Mehmet Akıf; Risvanli, Ali; Safak, Tarik; Yılmaz, Öznur; Yüksel, Burak Fatih; Şeker, İbrahim (My University, 2022)
In this study, it was aimed to determine asprosin levels in pregnant and non-pregnant cows and to determine the relationship between some biochemical parameters and asprosin levels. For this purpose, 60 Simmental cows were divided into two groups as pregnant (n=30) and non- pregnant cows on the postpartum 15th day (n=30), and asprosin levels and biochemical parameters were measured by taking blood from the cows once. Measured biochemical parameters were Alkaline phosphatase (ALP), Amylase, Creatine kinase myocardial band (CK-MB), Creatine kinase N-acetyl cysteine (CK-NAC), Gamma glutamyl transferase (GGT), Aspartate Aminotransferase (AST), Alanine aminotransferase (ALT) ), Direct bilirubin, Total bilirubin , Calcium (Ca), Choline (CHO), Creatine, Glucose, Total protein, Urea, Albumin, Iron, Phosphorus, Lactate dehydrogenase (LDH-P), High-density lipoprotein cholesterol (HDL-C) ), Low-density lipoprotein (LDL), Triglyceride, Magnesium (Mg) and Unsaturated iron binding capacity (UIBC). Asprosin levels were measured using commercial ELISA kits and biochemical parameters were measured in an autoanalyzer. Asprosin levels and biochemical parameters were compared both within and between groups and the results were evaluated. As a result of the data obtained, the amount of direct bilirubin and total bilirubin in non-pregnant cows was found to be higher than that of pregnant cows, while the amounts of CHO, HDL-C, LDL and asprosin were found to be lower. When asprosin and biochemical parameters of pregnant cows were compared, a positive correlation was found between asprosin and albumin, direct bilirubin, total bilirubin and creatinine levels. In non-pregnant cows, there was a negative correlation between asprosin and amylase and phosphorus, and a positive correlation between asprosin and creatine and glucose. As a result, it was concluded that asprosin levels are higher in pregnant cows and there may be negative or positive correlations between this hormone and biochemical parameters. However, it would be beneficial to carry out more comprehensive studies on the subject in order to reach more definite conclusions.
Keywords: Cow; Pregnancy; Biochemical parameters; Asprosin; Simmental.